John Steinbeck at Stonehenge - Unknown:::Creator:::::::::::: (2022)
John Steinbeck at Stonehenge, a prehistoric monument on Salisbury Plain in Wiltshire, England, two miles (3 km) west of Amesbury. Steinbeck visited here while staying in Discove Cottage, Somerset, England, while working on The Acts of King Arthur and his Noble Knights. Original in safe.